A new Hasemania Ellis from the upper rio Paraná basin, with the redescription of Hasemania crenuchoides Zarske & Géry (Characiformes: Characidae) - Serra, Jane Piton; Langeani, Francisco [UNESP] (FapUNIFESP (SciELO), 2015)
A new Hasemania species is described from the headwaters of the rio Uberaba, rio Grande basin, State of Minas Gerais, Brazil. The new species is distinguished from its congeners by a combination of a black, vertically-elongate humeral spot, a single ossification in the position primitively occupied by infraorbitals four and five, four teeth on the inner series of premaxilla, and scales covering the anal-fin base. Hasemania crenuchoides is redescribed and its known geographic distribution is extended; it can be differentiated from other species of the genus by the combination of a black verticallyelongate humeral spot, ii,8 dorsal-fin rays, 11-14 branched anal-fin rays, the presence of separate infraorbitals four and five, and the presence of scales covering the anal-fin base. Phylogenetic relationships of H. crenuchoides and the new species within Hasemania are discussed.
Keywords: Freshwater fish; Headwaters; Rio grande; Rio uberaba